2012
DOI: 10.1523/jneurosci.5275-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Synapsin I Phosphorylation Participates in the Expression of Post-Tetanic Potentiation and Its Enhancement by BDNF

Abstract: A large amount of experimental evidence has highlighted the rapid changes in synaptic efficacy induced by high-frequency stimulation and BDNF at central excitatory synapses. We clarified the quantal mechanisms and the involvement of Synapsin I (SynI) phosphorylation in the expression of post-tetanic potentiation (PTP) and in its modulation by BDNF in mouse glutamatergic autapses. We found that PTP is associated with an elevation in the probability of release and a concomitant increase in the size of the readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 56 publications
3
52
0
1
Order By: Relevance
“…Synapsin I isoforms are likely to be important for the presynaptic BDNF response, because BDNF causes synapsin Ia to be phosphorylated at MAPK phosphorylation sites Ser 62, Ser 67 and Ser 549 (Jovanovic et al, 1996) and deletion of the synapsin I gene abolishes the enhancement of glutamate release by BDNF in synaptosomes (Jovanovic et al, 2000). It remains possible that isoforms other than synapsin I may also be involved: the acute enhancement of evoked EPSCs by BDNF is intact in synapsin I KO neurons, as well as in synapsin I KO neurons expressing loss-of-function mutations in synapsin I MAPK phosphorylation sites (S62A, S67A; Valente et al, 2012). Ser 470 in synapsin IIIa has also been determined to be a substrate for MAPK (Porton et al, 2004), though whether this site is phosphorylated in response to BDNF is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Synapsin I isoforms are likely to be important for the presynaptic BDNF response, because BDNF causes synapsin Ia to be phosphorylated at MAPK phosphorylation sites Ser 62, Ser 67 and Ser 549 (Jovanovic et al, 1996) and deletion of the synapsin I gene abolishes the enhancement of glutamate release by BDNF in synaptosomes (Jovanovic et al, 2000). It remains possible that isoforms other than synapsin I may also be involved: the acute enhancement of evoked EPSCs by BDNF is intact in synapsin I KO neurons, as well as in synapsin I KO neurons expressing loss-of-function mutations in synapsin I MAPK phosphorylation sites (S62A, S67A; Valente et al, 2012). Ser 470 in synapsin IIIa has also been determined to be a substrate for MAPK (Porton et al, 2004), though whether this site is phosphorylated in response to BDNF is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Patch-clamp recordings from dissociated cultured hippocampal neurons and acute hippocampal slices Patch-clamp recordings were performed on cultured pyramidal neurons as previously described (Valente et al, 2012). Cultured pyramidal neurons were morphologically identified by their teardrop-shaped somata and characteristic apical dendrite after 12-16 div (Watt et al, 2000;Pratt et al, 2003).…”
Section: Mea Recordings and Analysis Of Neuronal Network Firing Activitymentioning
confidence: 99%
“…The C domain likewise contains such a candidate membrane-binding region, while other sites within the C domain appear responsible for binding to Actin filaments. These insights into Synapsin function were subsequently enriched in a number of ways (Benfenati, 2011): (1) Concomitant with the discovery of the requirement of Synapsin in non-associative short-term plasticity in Aplysia (Humeau et al, 2001), it was shown that serotonin induces Synapsin phosphorylation in Aplysia (Angers et al, 2002), likely via the cAMP-PKA pathway (Fiumara et al, 2004; see also Dolphin and Greengard, 1981) and/or the MAP kinase pathway (Giachello et al, 2010), and that these processes impact nonassociative short-term plasticity (Fioravante et al, 2007;Doussau et al, 2010;Giachello et al, 2010;Valente et al, 2012). Strikingly, it was recently reported that the synapsin gene of Aplysia features a CRE-recognition site, that serotonin induces de novo synthesis of Synapsin via the CREB1 pathway, and that this is required for nonassociative long-term plasticity (Hart et al, 2011).…”
Section: Synapsin Function Backgroundmentioning
confidence: 99%